ECOLOGY OF THE BLUE CRAB PORTUNUS PELAGICUS (LINNAEUS) AND ITS POTENTIAL FISHERY IN ZUARI ESTUARY - Dhawan, Rajinder M; Dwivedi, S N; Rajamanickam, G Victor (Indian Journal of Fisheries, 2011)
The occurrence of the tblue cra’b Portill/IIS peiagicils was studied from December 1972 to April 1973 in Zuari estuary. Environmerital parameters, ’liz., temperature, saHnity, oxygen, light penetpation and nature of bottom wer also 9tudied. 4519 Crabs were caught in 26 trawls; the males were 67.54% and the females were 32.46%. The dominant size groups for males ’and females were 115 mm and 105 mm, respectively. Females mature at a smaller size and breeding Mkes place during February-March. The widthlweight reitationship study show, d that females were heavier. The ’regression equation for female is: weight = 4.233 x 10-9 x L 4.969, and for male is: we:ght = 2.750 x 10-6 x L 3,636. The crabs were found to prefer loamy soil. The crab Portlll1l1S pefagiclIs constitutes a good food resource in the moutl>, region of Zuari estuary.